1992
DOI: 10.1109/34.177387
|View full text |Cite
|
Sign up to set email alerts
|

Separability of spatiotemporal spectra of image sequences

Abstract: SummaryWe calculated the Spatiotemporal power spectrum of 14 image sequences in order to determine the degree to which the spectra are separable in space and time, and to assess the validity of the commonly used exponential correlation model found in the literature. We expand the spectrum by a Singular Value Decomposition into a sum of separable terms and define an index of Spatiotemporal separability as the fraction of the signal energy that can be represented by the first (largest) separable term. All spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…It has also been shown that the pattern of change over time follows a power law. That is, if the contrast modulation over time for a given pixel is examined, the power spectra can also be modelled with P = 1/ f α , where P is the power as function of frequency f , and α is temporal spectral slope [BGK01, DA95, EBW92]. Temporal spectral slopes between 1.2 and 2.0 have been reported for natural image sequences.…”
Section: Second‐order Statisticsmentioning
confidence: 99%
“…It has also been shown that the pattern of change over time follows a power law. That is, if the contrast modulation over time for a given pixel is examined, the power spectra can also be modelled with P = 1/ f α , where P is the power as function of frequency f , and α is temporal spectral slope [BGK01, DA95, EBW92]. Temporal spectral slopes between 1.2 and 2.0 have been reported for natural image sequences.…”
Section: Second‐order Statisticsmentioning
confidence: 99%
“…Figure 7 shows how tracking modifies the instanta neous temporal frequency bandwidth in the region of tracking. The instantaneous temporal frequency band width was computed from the frame to frame correla tion, px, using a correlation model of the form = e -"M (Jayant & Noll 1984;Eckert et al 1992). For a frame rate of 30 frames per second, the temporal bandwidth can be computed as a = -3 0 log(pT).…”
Section: The Effect Of Tracking On Digitized Image Sequencesmentioning
confidence: 99%
“…A spatial and temporal response factorization was also performed similar to the method described by Mourão-Miranda et al [11]. Some previous studies have assessed formally the issue of separability [11,23]. Spatiotemporal factorization is an assumption implicit in conventional unsupervised approaches like ICA.…”
Section: Discussionmentioning
confidence: 99%